Combining Probability Forecasts: 60% and 60% Is 60%, but Likely and Likely Is Very Likely - Mislavsky, Robert; Gaertig, Celia (Management Science, 2022)
How do we combine others’ probability forecasts? Prior research has shown that when advisors provide numeric probability forecasts, people typically average them (i.e., they move closer to the average advisor’s forecast). However, what if the advisors say that an event is “likely” or “probable?” In eight studies (n = 7,334), we find that people are more likely to act as if they “count” verbal probabilities (i.e., they move closer to certainty than any individual advisor’s forecast) than they are to “count” numeric probabilities. For example, when the advisors both say an event is “likely,” participants will say that it is “very likely.” This effect occurs for both probabilities above and below 50%, for hypothetical scenarios and real events, and when presenting the others’ forecasts simultaneously or sequentially. We also show that this combination strategy carries over to subsequent consumer decisions that rely on advisors’ likelihood judgments. We discuss and rule out several candidate mechanisms for our effect. This paper was accepted by Yuval Rottenstreich, decision analysis.